ABOUT THE INSTITUTIONAL ENVIRONMENT OF FORMATION OF INTELLECTUAL CAPITAL IN MODERN ECONOMY - Natalya Kharchenko (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the essence of intellectual capital in the modern economy, analyze its composition and structure. The conclusion about the necessity of taking into account institutional approach to the examination ofprocesses of formation of intellectual capital in the modern economy. It shows the influence of the institutional environment on the formation of intellectual capital in the modern economy. The selected levels of intellectual capital, formed through the inluence of institutional factors. The necessity of creation in the economy and healthy competition as the basic condition of transition to the innovative way of development.